Employing the Technology Readiness Index (TRI) to Evaluate Customer Readiness for Future Adoption of The Metaverse in Virtual Branch Digital Banking Services - Wijanarko, Andang; Syafitri, Arinda; Andreswari, Desi (CV. Cendekiawan Muda Sriwijaya, 2024)
Metaverse banking integrates traditional financial services within a virtual environment, enabling alternative transaction channels through augmented reality (AR) and virtual reality (VR). By 2030, it is projected that nearly all bank clients will utilize these technologies for banking transactions. Although existing studies have explored metaverse adoption, there remains a significant research gap regarding client readiness for this transition. This study addresses this gap by examining customer readiness for metaverse banking using a quantitative approach. Data were collected through questionnaires distributed to 100 respondents in Bengkulu, Indonesia, and analyzed using the Technology Readiness Index (TRI) and SmartPLS 4 software. The findings indicate that customers in Bengkulu exhibit a readiness for virtual digital banking services in the metaverse, with a TRI score of 2.37 among respondents in the low technology readiness category. This score reflects a generally optimistic and innovative attitude toward metaverse banking, although accompanied by concerns about technological security. The